Quality Characteristics of Salted Layur Fish (Trichiurus sp.) Case Study: Johan Pahlawan, West Aceh - Akbardiansyah, Akbardiansyah; Ukhty, Nabila; Misbah, Iyan Al; Nafsiyah, Ikromatun (Universitas Teuku Umar, 2024)
Layur fish (Trichiurus sp.) is an important fishery commodity widely utilized as salted fish. However, traditional processing methods are susceptible to microbial and physical contamination, often failing to meet Indonesian National Standard (SNI) quality criteria.1 This study aimed to determine the quality characteristics of salted Layur fish produced in Johan Pahlawan District, West Aceh, based on SNI parameters, including salt content, moisture content, ash content, acid-insoluble ash content, and total plate count (TPC).1 An observational research method was employed, involving sampling from two salted fish vendors (Vendor A and Vendor B), followed by laboratory testing, and descriptive quantitative data analysis. The research results indicated that the salt content of salted Layur fish (Vendor A: 11.91%; Vendor B: 10.25%) and moisture content (Vendor A: 12.69%; Vendor B: 25.63%) met the requirements of SNI 8273:2016 (salt content 12.0–20.0%; moisture content max. 40.0%).1 TPC values (Vendor A: 0.00 CFU/g; Vendor B: 6.16 CFU/g) were also below the SNI 8273:2016 threshold (max. 1x10^5 CFU/g).1 However, the acid-insoluble ash content (Vendor A: 1.40%; Vendor B: 1.75%) significantly exceeded the maximum limit of SNI 2354-1:2010 (0.3%).1 The quality of salted Layur fish from Johan Pahlawan met SNI standards for salt content, moisture content, and TPC, but failed to meet the standard for acid-insoluble ash, indicating physical contamination that requires further attention